A novel splicing variant in NBAS identified by minigene assay causes infantile liver failure syndrome type 2 - Hu, Anna; Liang, Jun; Liu, Hongbo; Jiang, Jinghui; Xie, Fujing; Zhou, Xin; Zhang, Xiaojia (Frontiers in Genetics, 2025)
BackgroundInfantile liver failure syndrome type 2 (ILFS2) is an autosomal recessive disorder caused by biallelic NBAS variants, characterized by recurrent acute liver failure (ALF) typically triggered by febrile episodes.MethodsTrio-based whole-exome sequencing (Trio-WES) was performed on a child with recurrent ALF and both parents. Candidate variants were validated in family members by Sanger sequencing, and the functional impact of a novel splice-site variant was assessed using a minigene splicing assay.ResultsTrio-WES revealed compound heterozygous NBAS variants in the proband: the known pathogenic variant c.3596G>A (p.Cys1199Tyr) and a novel splice-site variant c.1600-1G>T. The c.1600-1G>T variant was classified as pathogenic based on ACMG criteria, supported by SpliceAI analysis predicting potential splicing abnormalities with the following scores: acceptor gain (AG = 0.33 at −9 bp), acceptor loss (AL = 0.93 at −1 bp), donor gain (DG = 0.00 at −8 bp), and donor loss (DL = 0.25 at −126 bp). Minigene assays confirmed that c.1600-1G>T causes aberrant pre-mRNA splicing, resulting in multiple abnormal transcripts—including 185 bp and 56 bp intron 15 retention, an 8 bp deletion within exon 16, and full exon 16 skipping—predicted to produce truncated or internally deleted NBAS proteins, providing functional evidence of pathogenicity.ConclusionWe report a novel pathogenic splicing variant in NBAS that causes ILFS2 in compound heterozygosity. This finding underscores the importance of integrating genomic sequencing with functional validation for accurate diagnosis and genetic counseling.